Influence of store image congruity on perceived risk of products. - Chan, Li Yan. (2010)
This paper explores the interactivity of retail store environmental cues on consumers’ perceived risk on merchandise offered under the particular environment. An empirical study examines all three types of environmental factors of ambient, social and design and their degree of congruency to the expected norm of a computer store environment in Singapore. Purchase intentions were also measured to investigate how any interaction between the two consumer behavior theories lead to practical differences. Results indicate that the different components of perceived risks vary differently with the congruity of store environment, while the moderate incongruity effect has also been proven to exist between congruency of store environment and purchase intentions of merchandise offered. In particular, financial risk had been observed to be the most influenced by the degree of congruency of environmental cues to the norm whereas time risk had been found to exhibit opposing results of increasing with increasing congruency. The results also provided future research possibilities into this relatively under-researched field of interaction between store design congruency and impact on perceived risks of merchandise offered.